2017
DOI: 10.1037/hum0000059
|View full text |Cite
|
Sign up to set email alerts
|

Self-esteem and body image in females: The mediating role of self-compassion and appearance contingent self-worth.

Abstract: Brett Carter attained his Bachelor of Psychological Science degree at Bond University in Australia. He is currently pursuing postgraduate research in Health Psychology and physiology, with a particular interest in curbing the trajectory of obesity prevalence rates. Brett is also an elite level swimming coach and former professional triathlete. Aileen Pidgeon is an Assistant Professor of Clinical Psychology and a board registered clinical psychologist with over 20 years clinical experience. She has had extensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 78 publications
(148 reference statements)
0
11
0
Order By: Relevance
“…Second, although previous studies of Cornelissen and co-authors(Cornelissen et al 2015 , 2017 ; Irvine et al, 2018) demonstrated that attitudinal components of body image can be compressed into a single principal component reflecting variation in attitudes to body shape, weight and eating, self-esteem and tendency to depression, yet in this study we did not include a measure of self-esteem and depression which could have mediated the need to appear thinner. With these regards, albeit no evidence for a specific role of self-esteem has been reported when investigating specific age-related differences in perceptual body image in previous investigations, yet it would be interesting to investigate in the future the link between self-esteem and body image concerns (Stapleton et al 2017 ), as well as repeated dieting behaviours in older women.…”
Section: Discussionmentioning
confidence: 97%
“…Second, although previous studies of Cornelissen and co-authors(Cornelissen et al 2015 , 2017 ; Irvine et al, 2018) demonstrated that attitudinal components of body image can be compressed into a single principal component reflecting variation in attitudes to body shape, weight and eating, self-esteem and tendency to depression, yet in this study we did not include a measure of self-esteem and depression which could have mediated the need to appear thinner. With these regards, albeit no evidence for a specific role of self-esteem has been reported when investigating specific age-related differences in perceptual body image in previous investigations, yet it would be interesting to investigate in the future the link between self-esteem and body image concerns (Stapleton et al 2017 ), as well as repeated dieting behaviours in older women.…”
Section: Discussionmentioning
confidence: 97%
“…First, consistent with expectations, global self‐esteem in college women was negatively associated with self‐worth based on one's appearance, which in turn, was related to greater drive for thinness and bulimic symptoms. This finding is in line with those of Bardone‐Cone et al (2017) and other studies that have connected appearance‐based self‐worth to negative body image and multiple related outcomes (e.g., body image disturbances; Siegel, Huellemann, Hillier, & Campbell, 2020; Stapleton, Crighton, Carter, & Pidgeon, 2017; Zeigler‐Hill & Noser, 2015). Indeed, as Mintz and Betz (1988) suggested over three decades ago, low global self‐esteem may be linked to eating disorders in women as a result of a society that impresses upon women the notion that their value to themselves and to society largely stems from their thinness and appearance.…”
Section: Discussionmentioning
confidence: 99%
“…(2015) and has also been shown to be a mediator in the relationship between several psychological factors and well-being, e.g. neuroticism and physical appearance anxiety ( Xu et al., 2017 ), self-esteem and body-image avoidance ( Stapleton et al., 2017 ), or behavior changes in well-being in 1 st year university students ( Gunnell et al., 2017 ). Therefore, the present research finding that self-compassion mediates the relationship between materialism and well-being is consistent with other domains.…”
Section: Discussionmentioning
confidence: 99%